2017
DOI: 10.7554/elife.24695
|View full text |Cite
|
Sign up to set email alerts
|

Domestic chickens activate a piRNA defense against avian leukosis virus

Abstract: PIWI-interacting RNAs (piRNAs) protect the germ line by targeting transposable elements (TEs) through the base-pair complementarity. We do not know how piRNAs co-evolve with TEs in chickens. Here we reported that all active TEs in the chicken germ line are targeted by piRNAs, and as TEs lose their activity, the corresponding piRNAs erode away. We observed de novo piRNA birth as host responds to a recent retroviral invasion. Avian leukosis virus (ALV) has endogenized prior to chicken domestication, remains infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 123 publications
(150 reference statements)
1
57
0
Order By: Relevance
“…Small RNA profiling also revealed abundant viral-derived piRNAs in Drosophila cell culture-thought to reflect naturally occurring infections (Wu et al 2010)-but not in actual flies subjected to experimental viral infection (Petit et al 2016). Chickens that harbor endogenized avian leukosis virus (ALV) sequences also produce copious amount of piRNAs from these loci in their testes (Sun et al 2017). Since one of these ALV loci, ALVE6, has been historically associated with ALV resistance (Robinson et al 1981), it is tempting to speculate that piRNAs derived from this locus offer antiviral protection.…”
Section: Pirnas Function Beyond Te Silencing and Outside The Germlinementioning
confidence: 99%
“…Small RNA profiling also revealed abundant viral-derived piRNAs in Drosophila cell culture-thought to reflect naturally occurring infections (Wu et al 2010)-but not in actual flies subjected to experimental viral infection (Petit et al 2016). Chickens that harbor endogenized avian leukosis virus (ALV) sequences also produce copious amount of piRNAs from these loci in their testes (Sun et al 2017). Since one of these ALV loci, ALVE6, has been historically associated with ALV resistance (Robinson et al 1981), it is tempting to speculate that piRNAs derived from this locus offer antiviral protection.…”
Section: Pirnas Function Beyond Te Silencing and Outside The Germlinementioning
confidence: 99%
“…For example, some EBLNs in rodents and primates appear to have inserted into piwi-interacting RNA (piRNA) genomic clusters and as a result produce piRNA-like RNAs in the testis [40]. Similarly, chickens also exhibit testis-specific piRNA expression, which appear to mostly map to young ALV derived ERV insertions, some of which are known to produce infectious viral particles [41]. It has been proposed that these small RNAs offer some protection to the host by silencing exogenous viral mRNAs [16,40,41].…”
Section: Eve As Restriction Factors: Fighting Fire With Firementioning
confidence: 99%
“…Similarly, chickens also exhibit testis-specific piRNA expression, which appear to mostly map to young ALV derived ERV insertions, some of which are known to produce infectious viral particles [41]. It has been proposed that these small RNAs offer some protection to the host by silencing exogenous viral mRNAs [16,40,41]. It has also been reported that elevated levels of ERV-derived RNAs leads to the accumulation of cytosolic nucleic acids, including double-stranded RNAs and complementary DNAs, which are recognized by nucleic acid sensors that direct cells to mount an antiviral and inflammatory response [4244].…”
Section: Eve As Restriction Factors: Fighting Fire With Firementioning
confidence: 99%
“…However, SSCs are rare in the adult testis (less than 0.1%), and the changes of sncRNAs in the SSCs upon mHen1 knockout were completely masked by the signal from other abundant cells in the testis. To explore the mHen1 substrates in mouse SSCs, we carried out sodium periodate (NaIO 4 )-assisted deep sequencing, a method previously used to investigate piRNA methylation (26,27). We generated mHen1 knockout SSC lines by the CRISPR/Cas9 method as well as Mili (a piRNA-binding protein indispensable for piRNA biogenesis) knockout SSC lines ( Fig.…”
Section: Hen1-dependent Methylation Of Pirnas In Sscsmentioning
confidence: 99%